Characteristics Associated with Anxiety in Cervical Cancer Patients Undergoing Chemotherapy Programs at Dadi General Hospital, Purwokerto Family - Maya Ade Kusniarti Pasaribu; Atun Raudotul Marifah; Siti Haniyah (Jurnal Berita Ilmu Keperawatan, 2023)
Cancer is the second biggest cause of death in women is cervical cancer. Cervical cancer is closely related to pain and anxiety, symptoms and effects of cervical cancer treatment are the main factors that affect anxiety, decreased physical condition, quality of life and relationships with family. The purpose of this study was to determine the characteristics associated with anxiety in cervical cancer patients who followed the chemotherapy program. The research method used is quantitative with analytical descriptive research design. The study was conducted using a cross sectional approach, the population in this study was 37 patients. This study used the instrument of Depression, Anxiety, Stress Scale-14 (DASS14) and used the Chi-Square Test. The results of the study showed that the anxiety level of chemotherapy patients at Dadi Keluarga Hospital was in severe anxiety, there was no relationship between age, education level, and income on the anxiety of chemotherapy patients at Dadi Keluarga Hospital, Purwokerto